First report of Vitis cryptic virus from grapevines in China - Fan, Xudong; Dong, Yafeng; Zhang, Zunping; Ren, Fang; Hu, Guojun (Plant disease, 2022)
Vitis cryptic virus (VCV) was recently identified on wild Vitis coignetiae in Japan in 2021, and was tentatively classified as a new member of the genus Deltapartitivirus, which is consistent with the two-segmented genome encoding RdRp and CP (Nabeshima et al., 2021). In June 2020, a grapevine cv. Jinhuanghou in a vineyard exhibiting chlorotic mottling (Figure S1) was collected in Xingcheng, Liaoning province of China. Total RNAs were extracted using RNAprep Pure Plant Plus Kit (DP441, TIANGEN BIOTECH, Beijing), and the ribosomal RNA were removed by the Epicentre Ribo-Zero rRNA Removal Kit (Epicentre, Madison, WI, USA). The ribosomal RNA-depleted RNA was then used to construct a cDNA library using a TruSeq RNA Sample Prep Kit (Illumina, San Diego, CA, USA), which was sequenced on an Illumina NovaSeq 6000 platform (Biomarker Biology Technology), resulting 60,208,348 paired-end clean reads (150 nt × 2). Reads mapping to the grapevine genome (PN40024 assembly 12X) were removed by hierarchical indexing using hisat2 2.1.0 software (Kim et al., 2019). The unmapped reads were de novo assembled into 116,809 contigs using the rnaviralSPAdes method in the SPAdes v3.15.3 software with default parameters (Prjibelski et al., 2020) and analyzed through BLAST analysis. Two viruses and two viroids were identified: VCV (2 contigs), grapevine emaravirus A (GEVA; 5 contigs), grapevine yellow speckle viroid 1 (GYSVd1; 1 contig) and hop stunt viroid (HSVd; 1 contig). The two contigs of VCV had lengths of 1575 nt and 1563 nt, and shared 95% and 90% nt identity with RNA1 and RNA2 genomes of the VCV isolate H1 (GenBank accession nos. LC602838-39) with 99% and 96% coverage respectively. To further confirm the infection of VCV, we designed two pairs of primers VCV-RP1a/1b (5'- TGGTCGAGAAGTTACTATACTCG -3'/5'- AGACCACAATATTGCTTTGGCTC -3') and VCV-CP1a/1b (5'-TTACGAAGTCCGCACTATTGC-3'/5'- AGCATACGGATAGCTCCTGAC-3'), which were to amplify the 297-bp and 279-bp fragments in the RdRp and CP gene encoded by RNA1 and RNA2 genomes of VCV respectively. The amplified PCR products were cloned and sequenced and the two sequences (OM460075-76) showed 93% and 91% nt identity with the genomic segments of the VCV isolate H1 respectively. The graft transmissibility of VCV was assessed in July 2021 by grafting the VCV-infected grapevine buds onto 2-year-old VCV-free 'Beta'grapevine seedlings with four replicates, the leaves of the first bud below the grafting site behaved chlorotic mottling symptoms (Figure S2) and tested positive for VCV two months after grafting. To further determine the incidence and distribution of VCV in China, 470 grapevine samples of 71 cultivars were collected from 21 provinces and tested by RT-PCR using primers VCV-RP1a/1b and VCV-CP1a/1b. The results showed that 2.6% (12/470) of the samples tested positive with both primers, including 10 'Jinhuanghou' grapevines (Jilin province), 1 'Zuoyouhong' (Jilin province) and 1 'Куртсет' grapevine (Liaoning province). This is the second report of VCV in the world, and confirm the graft transmissibility of VCV for the first time. Given the VCV infectivity in the two important cultivars in Jilin province and strong graft transmissibility, it is necessary to further study its pathogenicity and its effect on grapes. Unveiling the presence of VCV in China contributes to understanding the occurrence of the virus and developing management measures should they become necessary.